Pembentukan Portofolio Saham Optimal Berbasis Model Sharpe - Atika Lusi Tania; Era Yudistira; Einde Evana; Trijoko Prasetyo; Winda Nur Afrita; Fajar Baradewa; Husna Nur Pujianto (Assyarikah: Journal of Islamic Economic Business, 2025)
The purpose of this study is to analyse how to optimise Islamic stock portfolios in Indonesia using the Sharpe model. Most studies only focus on comparing Sharpe ratios between portfolios without exploring in depth the geometric structure of the relationship between return and risk. Many studies assume stable capital market conditions. This model considers the dynamics of return and risk movements as well as the Sharpe angle and the use of Excel Solver. Most studies discuss conventional stocks, while this study examines sharia stocks. Based on calculations using Excel Solver, two assets with the largest angles, meaning the best performance, were obtained. The best stock combination using the Sharpe method was obtained with a code of 70% and 30%. This study contributes to the development of portfolio management literature by offering a geometric perspective in stock performance analysis based on the Sharpe model, particularly for sharia stocks in Indonesia.